Promising Approaches in Early Childhood Development : Early Childhood Development Interventions from Around the World - World Bank Group (World Bank, Washington, DC, 2017)
This guide was prepared by the Early Learning Partnership (ELP) team at the World Bank as a resource for policy makers and development professionals interested in improving access to high-quality Early Childhood Development (ECD) services. It brings together a selection of approaches to ECD that have been implemented with promising results in low- or middle-income countries (or both). The list of programs and approaches highlighted here is by no means exhaustive; rather, those cited have been selected based on (i) some evidence of their positive impact or documentation of their results and (ii) their relevance to common needs and questions posed by governments and World Bank staff working in ECD.